Lexical Phenomenon in Linguistics Theories - Muhammad Qodri (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2019)
Lexical is study of vocabulary and its meanings in one language or in a number of languages. Vocabulary is concerned mainly with derivation of words, structures, moral, syntactic connotations, idiomatic expressions, synonyms, and multiplicity of meanings. This research aimed to describe the lexical phenomenon in linguistic theories. The methodology used in this research was qualitative research method with the type of library research. The results of the research were the lexical theory is carried out in a number of procedures necessary to accomplish the lexicon of the language, acoustically, and not neglected widely.